Assessing the Management of Life Insurance Funds: A case of SIC Life Company Limited. - Abdullah, Moubarak Salefu (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters in Business Administration, June, 2011